Extension into the entrance channel of HIV-1 reverse transcriptase—Crystallography and enhanced solubility - Bollini, Mariela (2013)
Non-nucleoside inhibitors of HIV-1 reverse transcriptase (HIV-RT) are reported that feature extension into the entrance channel near Glu138. Complexes of the parent anilinylpyrimidine 1 and the morpholinoethoxy analog 2j with HIV-RT have received crystallographic characterization confirming the designs. Measurement of aqueous solubilities of 2j, 2k, the parent triazene 2a, and other NNRTIs demonstrate profound benefits for addition of the morpholinyl substituent.